2021
DOI: 10.3389/fneur.2021.633207
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and the Individualized Therapy of Vestibular Disorders

Abstract: Background: Vestibular disorders (VDs) are a clinically divergent group of conditions that stem from pathology at the level of the inner ear, vestibulocochlear nerve, or central vestibular pathway. No etiology can be identified in the majority of patients with VDs. Relatively few families have been reported with VD, and so far, no causative genes have been identified despite the fact that more than 100 genes have been identified for inherited hearing loss. Inherited VDs, similar to deafness, are genetically he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 91 publications
(94 reference statements)
0
19
0
Order By: Relevance
“…Gene therapy tools have progressed considerably [improved AAVs, new delivery strategies, emerging gene editing tools; see ( 49 , 89 , 239 – 241 )] and there is an urgent need for their clinical application to hearing and balance disorders. Consistent with the considerable phylogenetic gap between vestibular and cochlear organs, the intermediate step toward successful gene therapies for the inner ear is now being achieved, at least in preclinical animal models presenting balance deficits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene therapy tools have progressed considerably [improved AAVs, new delivery strategies, emerging gene editing tools; see ( 49 , 89 , 239 – 241 )] and there is an urgent need for their clinical application to hearing and balance disorders. Consistent with the considerable phylogenetic gap between vestibular and cochlear organs, the intermediate step toward successful gene therapies for the inner ear is now being achieved, at least in preclinical animal models presenting balance deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Like hearing loss ( 49 , 88 ), vestibular disorders may have multiple causes, including genetics, aging, drugs, immune and environmental factors (e.g., infections, noise exposure) ( 89 ). The prevalence of vestibular impairment is high in children and adults with sensorineural hearing loss (SNHL), between 20 and 70% ( 90 , 91 ).…”
Section: Vestibular Disorders Associated With Hearing Loss: Diversity...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that non-coding variants in CRKL were significantly associated with risk for conotruncal heart defects in individuals with 22q11.2DS (12). Many genes have been related to hereditary non-syndromic hearing loss and Ménière's disease (13)(14)(15)(16). It is therefore possible that rare variants in these genes could modify audiovestibular phenotype by interacting with TBX1 in 22q11.2DS.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mutations in the subunits of the Ca V 1.3 channel type and in its modulator protein CaBP2 originate the autosomal recessive deafness, while many mutations in Ca V 1.4 channels and in their modulator protein CaBP4 are associated with autosomal recessive congenital stationary night blindness (reviewed in [ 4 ]). Vestibular disorders such as type 2 episodic ataxia are caused by mutations in the P/Q-type channel [ 6 ], possibly at the level of the vestibular hair cells [ 7 ]. Therefore, it is of paramount importance to investigate the biophysical properties of these channels: a convenient model is the hair cells isolated from the rana esculenta labyrinth, because they are particularly large and robust, yet they are very similar to the other vertebrate hair cells, and this comestible species can be easily supplied by local dealers.…”
Section: Introductionmentioning
confidence: 99%